A Z-scheme ZnFe2O4/RGO/In2O3 hierarchical photocatalyst for efficient CO2 reduction enhancement. Issue 14 (28th February 2020) - Li, Jiadong; Wei, Feng; Dong, Changchang; Mu, Wei; Han, Xiaojun
Abstract : ZnFe2 O4 /RGO/In2 O3 hierarchical tubules as efficient light-driven photocatalysts for converting CO2 to CO and CH4 . Abstract : Indium oxide (In2 O3 )-based photocatalysts have great potential in photocatalytic CO2 reduction. Nevertheless, their photocatalytic activity is inhibited by rapid electron–hole recombination. Hence, a novel Z-scheme ternary hierarchical ZnFe2 O4 /RGO/In2 O3 photocatalyst is fabricated for photocatalytic conversion of CO2 to CO and CH4 . The CO production rate reaches up to 35.4 μmol g −1 under 4 h of illumination using a 20ZFO/10RGO/IO catalyst, which is 3.9 times and 9.8 times higher than those using bare In2 O3 and bare ZnFe2 O4, respectively. The CH4 production rate is 7.8 μmol g −1, which is 4.3 fold and 2.4 fold higher, respectively, compared to those from bare In2 O3 and bare ZnFe2 O4 . The enhancement of photocatalytic CO2 reduction was ascribed to a Z-scheme mechanism of the hierarchical catalysts by introducing RGO in-between In2 O3 and ZnFe2 O4 to promote charge separation and realize efficient utilization of the high-energy electrons and holes. The oxygen-defect of ZnFe2 O4 also facilitates the adsorption and activation of CO2 . This work provides new insights to design ternary In2 O3 -based hierarchical photocatalysts with a rational Z-scheme photocatalytic mechanism to improve the CO2 conversion efficiency.